(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
The regular interactions and balance of the relationship of prolactin, gonads and testicular hormones and their suitability ensure that the sperm is normal in males. So this study is an attempt to classify male infertility depending on WHO criteria of seminal changes and to evaluate serum Prolactin, Testosterone FSH and LH levels in the participants, also determine the association between serum Prolactin, Testosterone levels and subtypes of male infertility. This study involved three hundred infertile males having infertility more than one year (cases group) and three hundred age-matched fertile males with definite paternity in past two years (control group) were included to the study from Jan 2020 -Dec 2021 at Al-Kut Hospital, Infertility Center in the Alkut city. Serum levels of hormones were measured by electrochemiluminescense immunoassay technique. Approximately half of patient’s age ranged between 30- 39 years. Sixty eight percentage of cases complained from primary infertility. About 71.3% of patients had infertility duration between 1 - 5 years. This percentage decreased with increasing the infertility years. Most common infertile group was Asthenospermia (34.3%). A higher significant levels of serum Prolactin, FSH and LH found in cases than controls (p<0.001). However, the serum Testosterone levels was significantly lower in cases than controls (p<0.05). Moreover, serum Prolactin levels were found significantly elevated in all infertile subgroups (except Normospermic subgroup) compared to control group, while serum Testosterone levels were significantly decreased in all infertile subgroups (except Normospermic subgroup) compared to control group (p<0.05). So we conclude that; Poor spermatogenesis is associated with high serum Prolactin, FSH,LH levels and low serum Testosterone levels in patients with male infertility. Moreover, elevated serum Prolactin levels and decreased serum Testosterone levels were significantly associated with A, AT, OAT, Azoo and OA infertile males.